I need a help in such a problem and will greatly appreciate any suggestions.

I was taught, division of an equation by an expression which can be equal to zero can lead to missing roots. But I thought that this is not forbidden completely, cause always in such a situation I simply solved additional equation (which was a divider) and checked if its roots are roots of an initial equation. For example:

$$ (x + 2)^2 + x + 2 = 0 $$

Dividing this by $( x + 2 )$ gives

$$ x + 2 + 1 = 0 $$

so the root is $x = -3$, then I simply check whether the $ x + 2 = 0$ gives a root which fits the initial equation, and it does: $x = -2$.

I do not have a great experience in mathematics, but I solved a couple of hundreds of equations more complex than this and never had a trouble. But today I encountered this issue. Here is the equation:

$$ 3\sin(5z) -2\cos(5z) = 3 $$

I saw that $\cos(5z) = 0$ is the one of the solutions, but I divided all by it and got:

$$ \begin{align} 3\tan(5z) - 2 &= 3 \\ 3\tan(5z) &= 5 \\ \tan(5z) &= \frac{5}{3} \\ 5z &= \arctan(\frac{5}{3}) + \pi k , k \in \mathbb{Z} \\ z &= \frac{\arctan(\frac{5}{3}) + \pi k}{5}, k \in \mathbb{Z} \end{align} $$

the second root is:

$$ \begin{align} \cos(5z) &= 0 \\ z = \frac{\frac{\pi}{2} + \pi k}{5} &= \frac{\pi (1 + 2 k)}{10}, k \in \mathbb{Z} \end{align} $$

But the first one is not a real root for some reason. This was the first thing which confused me here, I knew that I can lose a root but I never found parasite ones in similar situations. I was taught that parasite roots can appear only when doing a multiplication by an expression which can be equal to zero or an exponentiation to an even exponent, not in the cause of a division.

The second confusion is the fact that I actually have lost some roots, cause the right solution from the textbook was (with the introduction of the so called auxiliary angle $\sqrt{3^2 + 2^2} = \sqrt{13} \implies \gamma = \arcsin(\frac{3}{\sqrt{13}})$):

$$ \begin{align} \underbrace{\frac{3}{\sqrt{13}}}_{\sin(\gamma)} \ sin(5z) - \underbrace{\frac{2}{\sqrt{13}}}_{\cos(\gamma)} \ cos(5z) &= \frac{3}{\sqrt{13}} \\ \sin(\gamma)\sin(5z) - \cos(\gamma)\cos(5z) &= \frac{3}{\sqrt{13}} \\ \cos(\gamma + 5z) &= -\frac{3}{\sqrt{13}} \\ z &= \pm \frac{1}{5}\arccos(-\frac{3}{\sqrt{13}}) - \frac{1}{5}\arcsin(\frac{3}{\sqrt{13}}) + \frac{2\pi k}{5} \end{align} $$

So I actually have two questions:

  1. Is it possible to lose roots permanently when dividing an equation by an expression which may be equal to zero ?
  2. Is it possible to gain parasite roots in such a case? Or in which situations they can appear in general, not only concerning division?


  • 3
    $\begingroup$ Instead of dividing, you should factorize. IE: the first equation is $(x+2)(x+2+1)=0$. That makes the "division by zero" problem disappear. $\endgroup$ – Valtteri Feb 14 '13 at 21:58
  • 2
    $\begingroup$ There’s another problem besides the algebra error that Ludolila pointed out: $\cos 5z=0$ is not a solution. $5z=\left(2n+\frac12\right)\pi$ is a set of solutions making $\cos 5z=0$ and $\sin 5z=1$, but $5z=\left(2n+\frac32\right)\pi$, which also makes $\cos 5z=0$, is not a set of solutions, because it makes $\sin 5z=-1$. $\endgroup$ – Brian M. Scott Feb 14 '13 at 21:59
  • $\begingroup$ @BrianM.Scott Yes, you're right, thanks. $\endgroup$ – Julien Feb 14 '13 at 22:03

You should have divided both sides of the equation by $\cos (5z)$, and you only divided the left side.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.